Nurturing Jawi Through Education: Mirroring Jawi Education in Aceh and Malaysia - Syukri Rizki (IKAT: The Indonesian Journal of Southeast Asian Studies, 2020)
As Jawi – the Arabic orthography used to write Malay language – deals with more challenges in this sophisticated era, it requires more severe acts of nurturing its existence, one of which, education. Inferred to be originated from Aceh, the massive dissemination of Jawi got through the Malay Archipelago countries, including Malaysia, where it, compared to other countries, receives better treatment for its development nowadays. This paper seeks to trace the origin of Jawi and its development in the light of education in Aceh and Malaysia. The findings reveal that Jawieducation in Malaysia has better developed with its outstanding features. Relevant journal articles, books, reports, and online pages are consulted to obtain the real picture of Jawi education in both countries. Positive innovations developed in Malaysian schools are expected to set a new benchmark for Jawi education in Aceh in particular and in other Indonesian provinces which are concerned over Jawi education like Riau, Islands of Riau, South Sumatera, North Sumatera, and Jambi.